The effect of hydrogen on the magnetostriction of rare-earth compounds TbxDy1-xFe2 - Nikitin, S. A.; Tereshina, I. S.; Touliakov, A. P.; Tereshina, E. A.; Verbetsky, V. N.; Salamova, A. A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
The crystal structure and the magnetic and magnetoelastic properties of TbxDy1-xFe2Hy (x = 0.27; 0.41; y ≤ 3) are investigated. The hydrides are obtained by the interaction of TbxDy1-xFe2 samples with hydrogen gas at room temperature. It is established that the hydrides have the same cubic type of structure as the parent compounds but the lattice parameter in the hydrides is larger than in the hydrogen-free samples. Both the Curie temperature and the magnetic moment decrease drastically as the hydrogen concentration increases. Measurements of the longitudinal l|| and transverse magnetostriction l^ are carried out in magnetic fields up to 12 kOe in the temperature range 78√300 K using strain gauges.The thermal expansion coefficients as a function of temperature are obtained for hydrides with high hydrogen concentration. The magnetostriction of hydrides is strongly different from that of hydride-free samples. The small and negative value of the magnetostriction at low temperatures proves that hydrogen atoms make a strong contribution to the crystal field acting on the rare-earth ions.